Seeking to Establish a Better Balance between the Technical and Social Aspects of Assessment Practices (London Journal of Research In Humanities and Social Sciences, 2023)
This article highlights the need for a better balance between the technical and social aspects of assessment in the English inspection system of state schools. The author compares the theoretical belief that underpins current assessment practice with that which would need to be given more credence if teachers and inspectors are to become part of the same community of practice. This focus is seen as relevant at a time when inspection is once again under scrutiny following the death of a headteacher after a critical OFSTED judgement. Although it is understandable that teachers’ reaction to this news is to call for the abandonment of inspections (NEU, 2023) an alternative scenario is offered that might allow all those involved in and with schools to become more equal partners in the evaluation process (Rorty,1991). By considering the different participants in terms of their ‘figured worlds’ (Holland et al, 1998) and introducing the concept of ‘roles by metaphor’ (Wiliam,2000) as part of the feedback process the author offers a non-confrontational means of opening a meaningful dialogue between inspectors and teachers with the intention of improving pupil learning and teacher planning. For this model to be effect teachers must change role from delivery person to coach or scaffolder to allow pupils to change role from in attendance to absorbent recipient for example or metacognitive reflector. Similarly, inspectors will need to cease exerting power over teachers  by changing role from judge to critical friend to communicate more effectively and lessen tension. Examples of how pedagogy and critical and social aspects of assessment affect pupil motivation, love of learning, independent thinking and grasp of subject matter are drawn from the writer’s experience of being part of the English state education system as a pupil, teacher, inspector, and researcher over the period 1949-2023 before sharing what happened when an inspection team trialled ‘roles by metaphor’ during a sixth form inspection.
Keywords: formative assessment; behaviourism; sociocultural theory; systems-rationalism; subjectivist-interpretivist; figured worlds; roles by metaphor